Pengaruh Locus of Control dan Stres Kerja terhadap Kepuasan Kerja Karyawan - Ira Ardyani; R Deni Muhammad Danial; Dicky Jhoansyah (IPM2KPE, 2022)
The purpose of this study was to determine the effect of locus of control and job stress in increasing employee job satisfaction at PT. FIFGROUP Sukabumi branch. The research method used in this research is quantitative. The data analysis method used is descriptive and associative analysis. The data analysis technique used is the validity test, reliability test, multiple linear regression analysis, including the coefficient of determination and multiple correlation coefficients. The results showed that the coefficient of determination test seen from the value (Adjusted R2) of 0.406 means that Locus of Control and Job Stress on employee job satisfaction is 40.6%. The remaining 59.4% is influenced by other factors outside of this study. The test value of the multiple correlation coefficient is seen from the R value of 0.653, which means that there is a moderate relationship between locus of control and job stress and employee job satisfaction. In conclusion, Locus of control and job stress affect employee job satisfaction. In the sense that the better the locus of control that occurs within the company, the job satisfaction of the employees in the company will be good or high and the better the work stress of the employees will also be better in completing their duties. Keywords: Employee Job Satisfaction, Locus of Control, Job Stress